Retrospective estimation of porbeagle Lamna nasus catches in the Spanish surface longline fishery targeting swordfish in the North Atlantic - Mejuto-García, Jaime; García-Cortés, Blanca; Ramos-Cartelle, Ana (2010)
Sí